Pensamento computacional na educação básica: uma proposta metodológica com jogos e atividades lúdicas - Meira, Ricardo Radaelli (2017)
The present dissertation entitled "COMPUTATIONAL THINKING IN BASIC EDUCATION: A METHODOLOGICAL PROPOSAL WITH GAMES AND LONDON ACTIVITIES" was carried out in the research line Development of Educational Technologies in Network, in the area of concentration Educational Technologies in Network for Innovation and Democratization of Education, in the course Master's Degree in Networked Educational Technologies, at the Federal University of Santa Maria. This dissertation proposed to elaborate, apply and analyze a methodological proposal with games and play activities that seeks to stimulate the development of the Computational Thinking of elementary school students of a public school, through practical workshops, where the students are accompanied in the course of the proposed activities. Firstly, contextualizes computational thinking and its teaching in the educational field, the state of the art and the insertion of computational thinking in Basic Education. The games and play activities selected and used were Computational Thinking in Daily Life, The Pillars of Computational Thinking, Human Robot, Building Frankenstein, Story Building, Tower of Hanoi, Logic Blocks, Code Time and Scratch. The activities carried out resulted in an interaction between the studied group and the latter with the concepts of computational thinking, the tools used were analyzed on the view of knowledge developed by the students according to their use, and suggestions for use and improvement were presented. The research is characterized as qualitative and uses as a methodological procedure the field research, with the help of tools used in activities with and without computational resources. As final product, the methodology proposed in this dissertation is elaborated.